Touching America's History : From the Pequot War through WWII - Brown, Meredith M. (Book collections on Project MUSE., 2013)
Things you can see and touch can bring to mind the time when the items were made and used. In Touching America's History, Meredith Mason Brown uses twenty objects to summon up major developments in America's history. The objects range in date from a Pequot stone axe head probably made before the Pequot War in 1637, to the western novel Dwight Eisenhower was reading while waiting for the weather to clear so that the Normandy Invasion could begin, and to a piece of a toilet bowl found in the bombed-out wreckage of Hitler's home in the Bavarian alps in 1945. Among the other historically evocat.